THE POSITION OF DIGITAL EVIDENCE IN THE KUHAP EVIDENCE SYSTEM NORMATIVE ANALYSIS AND IMPLEMENTATION CHALLENGES - Muhammad Yasir (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The development of information technology has given rise to new forms of crime that utilize digital media, thus requiring specific regulations for digital evidence within the Indonesian criminal procedure system. The Criminal Procedure Code (KUHAP), as the primary legal instrument, does not explicitly address the definition and procedures for managing digital evidence, creating challenges in the investigation, prosecution, and presentation of evidence in court. This study discusses the definition and characteristics of digital evidence, the urgency of its regulation in the Criminal Procedure Code (KUHAP), the technical and legal challenges in its use, and a comparison of practices in other countries as material for evaluation and recommendations. The analysis shows that unclear regulations lead to legal uncertainty and potential human rights violations. Therefore, an update to the Criminal Procedure Code is needed to include specific provisions on digital evidence, including confiscation, security, and digital forensic validation. This update is deemed necessary to ensure effective law enforcement and protect the rights of suspects and defendants in Indonesia's digital era.